2008
DOI: 10.1063/1.2926632
|View full text |Cite
|
Sign up to set email alerts
|

Analytic, nonlinearly exact solutions for an rf confined plasma

Abstract: RF confined electron plasmas are of importance in Paul traps [W. Paul, Rev. Mod. Phys. 62, 531 (1990)]. The stability of such plasmas is unclear and statistical heating arguments have been advanced to explain the observed heating in such plasmas [I. Siemers et al., Phys. Rev. A 38, 5121 (1988)]. This study investigates the nature of a one-dimensional collisionless electron plasma that is confined by an rf field of the form [−B+Acos(ωt)]x, where x is the space coordinate and ω is the rf frequency. Nonlinearly e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
15
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 35 publications
0
15
0
Order By: Relevance
“…19, and it was found that the time-averaged plasma density is different from Eq. 19, and it was found that the time-averaged plasma density is different from Eq.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…19, and it was found that the time-averaged plasma density is different from Eq. 19, and it was found that the time-averaged plasma density is different from Eq.…”
Section: Introductionmentioning
confidence: 97%
“…9,10 And for the case of electromagnetic waves, one of the most active areas of research over the past decade has been laser wake-field acceleration. [19][20][21] For the case of an oscillatory electric field with a general spatial dependence, conventional ponderomotive theory 10,22-29 has been widely used to predict the time-averaged plasma density. [16][17][18] Under the influence of oscillatory electric fields, the distribution function and density of a plasma also have oscillatory components.…”
Section: Introductionmentioning
confidence: 99%
“…However, if the externally applied field is much stronger than the induced field, the latter can be ignored [16]. The Vlasov equation has been solved earlier for the case of a spatially linear time-periodic electric field and it has been found that the solutions are typically aperiodic in time, but can also be periodic for certain specific initial conditions [3,17]. This leaves open the question as to which of these infinitely many distributions obtained by solving the Vlasov equation actually gets manifested in an experimental setting.…”
Section: Introductionmentioning
confidence: 99%
“…Though the conventional ponderomotive theory has been widely used for the last few decades in describing plasma dynamics, it has been recently shown to have severe limitations. [13][14][15][16] Under certain conditions, it has been shown that instead of the square of the electric field, the plasma density depends on the square of the electric potential. 16 Thus, instead of Eq.…”
mentioning
confidence: 99%